2019
DOI: 10.1089/jmf.2018.0026
|View full text |Cite
|
Sign up to set email alerts
|

Which Plant Part of Purple Coneflower (Echinacea purpurea (L.) Moench) Should be Used for Tea and Which for Tincture?

Abstract: Medicinal plants are widely used for the relief of disease symptoms or as dietary supplements. In recent decades, purple coneflower has become extremely well known. An infusion or tincture of purple coneflower can be prepared by anyone simply, inexpensively, and ecologically safely. Three plant parts of purple coneflower were used in the study: extracts from roots, flowers, and leaves were obtained using three different solvents (100% and 40% ethanol and water). High-performance liquid chromatography-mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
3
23
0
3
Order By: Relevance
“…Crushing increases the surface area and the enhanced contact of plant material with the solvent, which allows a faster transfer of selected compounds across the cell membrane into the final product . However, this also depends on the location of these compounds (vacuole, nucleus or cell wall) . In ethanolic solution, phenolics need more time to transfer from the plants into the solvent, and phenolics in 40% ethanol reached higher values after 14 or 21 days of maceration than did plant material in the control treatment (80% MeOH).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crushing increases the surface area and the enhanced contact of plant material with the solvent, which allows a faster transfer of selected compounds across the cell membrane into the final product . However, this also depends on the location of these compounds (vacuole, nucleus or cell wall) . In ethanolic solution, phenolics need more time to transfer from the plants into the solvent, and phenolics in 40% ethanol reached higher values after 14 or 21 days of maceration than did plant material in the control treatment (80% MeOH).…”
Section: Resultsmentioning
confidence: 99%
“…(2008) reported that a concentration of organic solvent above 60% means higher protein coagulation, which causes greater diffusion resistance . Nevertheless, more polar phenolics in their chemical structure yielded the lowest content of pure organic solvent than in a mixture of solvents . This means that ethanol, with a lower percentage of organic solvent and a higher percentage of water, was better for extraction than 80% methanol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Main physiochemical properties of soil sample was given in Table 3. According to results, the soil had neutral reaction without salinity effect (EC less than 2 dS m −1 ) which is suitable for wide range of nutrients availability 20 . As well as, it had calcareous nature (more than 5% CaCO 3 at topsoil) with sandy clay loam texture.…”
Section: Resultsmentioning
confidence: 92%
“…All of them are able affect the free radical production and lipid peroxidation 6 . Recent studies also relevant that echinacoside and caffeic acid derivative have weak anti-bacterial and antiviral effects and are protectants against reactive oxygen species 20,39 . The antioxidant activity could be ascribed to the polyphenolic components 13 , such as flavonoids 34 , phenolic acids 35 or phenolic diterpenes 9 .…”
Section: Discussionmentioning
confidence: 99%